2022
DOI: 10.1055/a-1729-9664
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective C–H Functionalization toward Silicon-Stereogenic Silanes

Abstract: In recent years, transition-metal-catalyzed enantioselective C–H bond functionalization has emerged as a powerful and attractive synthetic approach to access silicon-stereogenic centers, which continues to give impetus for the innovation of chiral organosilicon chemistry. This short review is aimed to summarize recent advances in the construction of silicon-stereogenic silanes via transition-metal-catalyzed enantioselective C–H functionalization. We have endeavored to highlight the great potential of this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Also, it is non-toxic and has a unique electronic structure which makes iron even more attractive for developing new catalysts in this field. 36,37…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is non-toxic and has a unique electronic structure which makes iron even more attractive for developing new catalysts in this field. 36,37…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of new synthetic methods for the synthesis of silicon-stereogenic silanes has become an important research subject, given that these non-natural chiral molecules have shown attractive and broad application prospects in various areas . Among many elegant approaches, the desymmetrization of dihydrosilanes via catalytic asymmetric dehydrogenative coupling (Si-CADC) has emerged as a more efficient and straightforward tool for the access of diverse silicon-stereogenic silanes .…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Despite significant efforts spent in the development of nonprecious metal catalytic systems and progress made in this direction, platinum complexes remain commonly used catalysts for hydrosilylation processes. 4–29 However, platinum-catalyzed hydrosilylation has difficulties in controlling catalyst performance and insufficiently high selectivity of the process, which affect the overall costs of product formation. A better understanding of the catalytic reaction mechanism can provide a rational solution to these problems.…”
Section: Introductionmentioning
confidence: 99%